Knowledge attitude and practice of pharmacovigilance among nursing professionals in a tertiary care teaching hospital in Dehradun, Uttarakhand - Sharma, Taruna; Dhasmana, D. C.; Sharma, Rajendra; Bala, Suman; Sharma, Upasana; George, Upma (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacovigilance deals with identification, assessment and prevention and reporting of adverse drug reaction (ADR), play a pivotal role in ensuring safe use of drugs. However, in spite of having well established ADR reporting system in India and worldwide, the ADR underreporting is a big challenge till date. It is therefore very important to assess the level of awareness of Pharmacovigilance among healthcare professionals to identify the factors affecting ADRs reporting. The objective of the study was to evaluate knowledge, attitude and practice of pharmacovigilance among nursing professionals in a tertiary care teaching hospital in Dehradun, India. Methods: It was a cross sectional observational study conducted at HIMS over a period of 1 year. Nursing professionals who work in internal medicine, Surgery, PAC and intensive care unit (ICU) were included in this study. A self-administered questionnaire comprising of 15 items related to ADRs and Pharmacovigilance programme of India (PvPI) activity was provided to them and sufficient time to fill the questionnaire was given. The completely filled questionnaire was collected and data was analyzed using SPSS ver.20.0. Results: A total of 415 participants were included in the study. The mean age of the participant was 28.52 years. The number of female was more than male participants. Majority of participant (56%) couldn’t answer the meaning of pharmacovigilance. Only 25% participants were aware about ADR reporting process to ADR monitoring centre (AMC). Although majority of the participants understand the necessity of ADR reporting and aware about AMC centre and PvPI, but most of them showed unfamiliarity about ADR reporting form and previous experience of any kind of ADR. The most common reason for not reporting the ADR was difficulty in deciding the nature of adverse effects (AE) (44%) followed by lack of time (30%). Majority of participant (67%) denied any previous pharmacovigilance training and almost all (98%) have shown their interest in PvPI training. Conclusions: Nursing professionals in our hospital may lack adequate knowledge about ADR reporting and may need more education and training on the National Pharmacovigilance System and ADR reporting process.